2015
DOI: 10.1038/srep12903
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Carbon Nanosphere/NiCo2O4 Core-shell Sub-microspheres for High Performance Supercapacitor

Abstract: This paper introduced a process to prepare the carbon nanosphere (CNS)/NiCo2O4 core-shell sub-microspheres. That is: 1) CNSs were firstly prepared via a simple hydrothermal method; 2) a layer of NiCo2O4 precursor was coated on the CNS surface; 3) finally the composite was annealed at 350 °C for 2 hours in the air, and the CNS/NiCo2O4 core-shell sub-microspheres were obtained. This core-shell sub-microsphere was prepared with a simple, economical and environmental-friendly hydrothermal method, and was suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 38 publications
11
62
0
Order By: Relevance
“…The peaks located at 151.6, 457.6, 455.2, 505.7, 656.6, and 1096.4 cm −1 , respectively, correspond to F 2g , E g , L O , A 1g , and 2 L O modes of NiCo 2 O 4 , while the peak located at 501.3 cm −1 belongs to NiO. These results are well consistent with the previously reported literatures [18, 21, 24].
Fig.
…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The peaks located at 151.6, 457.6, 455.2, 505.7, 656.6, and 1096.4 cm −1 , respectively, correspond to F 2g , E g , L O , A 1g , and 2 L O modes of NiCo 2 O 4 , while the peak located at 501.3 cm −1 belongs to NiO. These results are well consistent with the previously reported literatures [18, 21, 24].
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…In general, EIS is usually used to investigate the performance of electrochemical capacitors, such as internal resistance and capacity [18, 19]. The EIS data were commonly analyzed by using Nyquist plots, in which the frequency response of the electrode/electrolyte system and the plots of the imaginary component ( Z ″) of the impedance against the real component ( Z ′) are presented [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the peaks at 780.7 and 795.8 eV are ascribed to Co 2+ while the other two peaks at 779.4 and 794.6 eV belong to Co 3+ . Thus, the XPS results demonstrated that the electron couples of Ni 3+ /Ni 2+ and Co 3+ /Co 2+ coexisted in NiCo 2 O 4 aerogel, which is consistent with the previously reported results for NiCo 2 O 4 10. The C 1s emission spectrum (Figure 3d) can be divided into four peaks centered at 284.6, 286.4, 287.8, and 289.0 eV, which is attributed to the C—C/C=C, C—O, C=O, and O=C—O groups,6 respectively.…”
supporting
confidence: 92%
“…Compared with other counterparts, transition metal oxides with nanostructural characteristics attracted wide attention due to their high surface-to-volume ratio and short path length for Li-ion diffusion [7][8][9]. Among transition metal oxides, cobalt oxide exhibited capacity 3 times higher than that of conventional graphite, but considering the high cost and toxic nature of cobalt, it has not been regarded as a suitable alternative anode material [10][11][12][13] [14][15][16][17][18]. With two different metal cations, these binary metal oxides exhibit high electrochemical characteristics due to their complicate chemical composition and synergic effects of multiple metal species.…”
Section: A N U S C R I P Tmentioning
confidence: 99%